Enforcement Of Administrative Sanctions For Violations Relates To Health Care Advertising And Publication - Aisyah Rahman Puspita; Hufron (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This research aims to understand the enforcement of administrative sanctions related to health promotion in Indonesia. This research is motivated by the increasing number of cases of the spread of misleading health information in the digital era, which can be detrimental to society, one of which is excessive claims made on TV broadcasts. These clinics are the White Herbal Clinic (aired on Jak TV), Zona Therapy Clinic (Elshinta TV and Jak TV) and Tramedica Clinic (Jak TV). Other violations in the advertisement include excessive claims that they are able to cure various types of diseases just by following therapy and consuming the medicine provided, using healing methods through herbs or medicines and actions whose benefits and safety have not been proven, apart from that it also presents testimonials from patients that appear to be If you managed to recover after following therapy and taking certain herbal medicines. It is clear that this case violates the Regulation of the Minister of Health of the Republic of Indonesia Number 1787/MENKES/PER/XII/2010. The method used in this research is normative juridical with a conceptual approach and analysis of applicable laws and regulations. The research results show that enforcing administrative sanctions against health service advertisements and publications requires synergy between various related agencies, such as the Food and Drug Monitoring Agency (BPOM), the Ministry of Health, and law enforcement officials. Coordination between these institutions is needed to overcome the challenges of monitoring health information, especially on digital platforms, as well as providing strict sanctions against perpetrators who are proven to have violated them. In addition, this research also found that public education about consumer rights in the health sector is an important key in creating safe and responsible health advertising and promotion.